A model of the oscillatory mechanical forces in the conventional outflow pathway. Issue 150 (30th January 2019) - Sherwood, Joseph M.; Stamer, W. Daniel; Overby, Darryl R.
Abstract : Intraocular pressure is regulated by mechanosensitive cells within the conventional outflow pathway, the primary route of aqueous humour drainage from the eye. However, the characteristics of the forces acting on those cells are poorly understood. We develop a model that describes flow through the conventional outflow pathway, including the trabecular meshwork (TM) and Schlemm's canal (SC). Accounting for the ocular pulse, we estimate the time-varying shear stress on SC endothelium and strain on the TM. We consider a range of outflow resistances spanning normotensive to hypertensive conditions. Over this range, the SC shear stress increases significantly and becomes highly oscillatory. TM strain also increases, but with negligible oscillations. Interestingly, TM strain responds more to changes in outflow resistance around physiological values, while SC shear stress responds more to elevated levels of resistance. A modest increase in TM stiffness, as observed in glaucoma, suppresses TM strain and practically eliminates the influence of outflow resistance on SC shear stress. As SC and TM cells respond to mechanical stimulation by secreting factors that modulate outflow resistance, our model provides insight regarding the potential role of SC shear and TM strain as mechanosensory cues for homeostatic regulation of outflow resistance and hence intraocular pressure.